Caracterização dos eventos reprodutivos em preás (Galea spixii Wagler, 1831) - Vale, Andre Menezes do (Brasil, 2017)
The gestation period, the characteristics of the reproductive cycle, including the selection of the influence of the male effect, the description of the female reproductive system, placentation, embryonic and fetal development – added of the morphometric analysis - and the expression of sulfated glycosaminoglycans (GAGs) in the reproductive and placental organs were the ways to contribute with the conservation of the species. For this, 45 non-pregnant females were used in the following experiments: 15 females were distributed in three experimental groups, followed by the addition of one male in each group, so that after the copulation and fertilization the females were separeted in accordance with the compatible dates of begining (days 5, 10 and 15), middle (days 20, 25, 30 and 35) and end (days 40, 45, 50 and 55) of gestation. This condition was obtained to obtain fragments of gestational sacs, placentas and organs of the female reproductive system, which were fixed in 4% paraformaldehyde and submitted to light microscopy techniques. The samples fixed in glutaraldehyde were performed in scanning and transmission electron microscopy techniques. In addition, prozima was used for GAG extraction, followed by agarose gel electrophoresis and subsequent quantification by densitometry. The second experiment consisted of the use of five females, housed in a room that contained a male to monitor the duration of gestation. The third experiment aimed to characterize the estrous cycle in a group containing five females plus one male, which was found trapped in a cage and another five, in a box exempt from the latter. The fourth experiment was performed by means of the morphometric analysis of embryos with 20, 25, 30 and 35 days plus fetuses on days 40, 45, 50, 55, 60 and newborns. The results revealed the presence of an incomplete double uterus, formed by two horns, a septate body and a cervix. The organs of the reproductive system presented macroscopic and histological characteristics similar to those reported for other rodents. The duration of gestation showed an average of 59 ± 2,7487 days and the sexual cycle was classified as continuous polystyric, with a mean period of 14.8 ± 0.73 days for females submitted to the male effect and 14.6 ± 0.75 days for those of the other group. In addition, the male presence significantly influenced (D <0.05) the duration of the diestrus, making it longer. The yolk sac inversion occurred on the 14th day of gestation and the visceral endoderm was placed in apposition to the uterine tissues. The chorioallantoic placenta presented a discoidal shape and had well defined regions of spongiotrophoblast, labyrinth and subplacenta from the intermediate gestation. Embryonic development was similar to that observed in histricognatis rodents, being the transition to the fetal phase, occurring at 40 days of gestation. Morphometric data allowed the establishment of correlations with gestational age. Dermatan sulfate was the predominant GAG in samples of uterine tubes, vaginas and placentas, whereas heparam expressed more in the body of the uterus at the beginning of gestation. There were also high concentrations of GAGs in the pregnant uterus and still in the reproductive system in the estrogenic phase when compared to the diestrus. It is concluded that the reproductive events presented characteristics of the species correlated with others of the order Rodentia, fact that indicates a set of evolutionary strategies related to its maintenance
Characterization of events reproductive in galea (Galea spixii Wagler, 1831)
Keywords: Sistema reprodutor feminino; Ciclo estral; Placentação; Embrião; Feto; Morfometria; Glicosaminoglicanos; Female reproductive system; Estrous cycle; Placentation; Embryo; Fetus; Morphometry; Glycosaminoglycans; CIENCIAS AGRARIAS::MEDICINA VETERINARIA